Borane‐Catalyzed Synthesis of Quinolines Bearing Tetrasubstituted Stereocenters by Hydride Abstraction‐Induced Electrocyclization. Issue 61 (5th October 2018) - Maier, Alexander F. G.; Tussing, Sebastian; Zhu, Hui; Wicker, Garrit; Tzvetkova, Pavleta; Flörke, Ulrich; Daniliuc, Constantin G.; Grimme, Stefan; Paradies, Jan
Abstract: The borane‐catalyzed synthesis of quinoline derivatives bearing tetrasubstituted stereocenters from vinyl anilines has been developed. Mechanistic studies and quantum‐mechanical investigations support the hydride abstraction/electrocyclization/hydride addition mechanism. The products were obtained in up to 99 % yield with a diastereoselectivity of >99 % in favour for the 3a‐5‐ cis isomer. Abstract : It′s all in the abstract : The borane‐catalyzed synthesis of quinoline derivatives bearing tetrasubstituted stereocenters from vinyl anilines has been developed. Mechanistic and quantum‐mechanical investigations support the hydride abstraction/electrocyclization/hydride addition mechanism. The products were obtained in up to 97 % yield with a diastereoselectivity of >99 % for the 3a‐5‐ cis isomer.